THU0217 DKK-1 Levels Are Elevated in Patients with Enthesitis Related Arthritis without Sacroiliac Joint Fusion. (15th July 2016) - Fisher, C.; Bourke, L.; Radziszewska, A.; Jadon, D.; Sengupta, R.; Bray, T.; Hall-Craggs, M.; Sen, D.; Ioannou, Y.
Abstract : Background: Dkk-1 is an inhibitor of the Wnt signalling pathway and therefore plays an important role in bone remodelling. Studies in adults with ankylosing spondylitis have described lower levels of Dkk-1 compared to healthy controls although this is not consistent. Higher levels have been found in some cohorts and particularly in patients with no syndesmophyte formation, suggesting that Dkk-1 may be an important factor in bony ankylosis. There has been no description of Dkk-1 in a younger population with enthesitis related arthritis (ERA). Objectives: To test serum Dkk-1 levels in adolescent and young adult patients with ERA and compare between different disease phenotypes and healthy controls. Methods: Patients were recruited from the adolescent and young adult clinics at University College London Hospital. Serum samples were stored at -80°C until use. Dkk-1 levels were measured by ELISA (Quantikine, R&D Systems, Minneapolis, MN) as per manufacturer's instructions, in duplicate and correlated with clinical features and MRI results. Results: Serum from 78 patients with ERA (median age 17 years) and 20 age and gender matched healthy controls was tested. Dkk-1 levels were significantly higher in patients with ERA (median=2971pg/ml, IQR 2258–3511pg/ml) compared to healthy controls (median=1806pg/ml, IQR 1307–2950pg/ml, p=0.0014) (Figure 1 A). Patients with ERA who were HLA-B27 positive had higher Dkk-1 levels (median=3081pg/ml, IQR 2337–3680) than those who were HLA-B27 negative (median=2445pg/ml, IQR 1832–3365, p=0.0488) (Figure 1 B). Interestingly, there was no significant difference in Dkk-1 levels between patients with axial and those with persistently peripheral ERA or between patients on TNF inhibitors versus those naïve to biologics. There was no correlation between Dkk-1 and CRP, ESR, patient age at date of sample or disease duration. Eleven patients with ERA of the 78 tested had already developed bony fusion of their sacroiliac joints (SIJs); in this group Dkk-1 levels were unexpectedly lower (median=2214pg/ml, IQR 2103–2618pg/ml) compared to those with ERA who had no evidence of bony fusion on MRI scan (median=3042pg/ml, IQR 2321–3607pg/ml, p=0.0355) (Figure 1 C). Conclusions: In our study, patients with ERA had significantly higher serum levels of Dkk-1 compared to controls. Levels were even higher in those patients who were HLA-B27 positive but there was no correlation with axial disease, patient age, disease duration, CRP, ESR or TNF inhibition treatment. Patients with existing bony fusion of their SIJs had lower levels of Dkk-1, despite the numbers being relatively small. Dkk-1 levels appear elevated in ERA but may reduce with the occurrence of bony fusion. Further larger and longitudinal studies are needed to confirm these findings and to correlate changes in Dkk-1 levels with treatment and MRI findings over time. Disclosure of Interest: None declared